Evaluación de tres ataques ransomware utilizando escenarios virtuales como plataforma experimental. - Aguilar Noblecilla, Daniel Alejandro (2018)
Ransomware is a type of malicious software intended to infect one or several devices within a network, giving the ability to a cybercriminal to encrypt the files and deny the user access to all the stored information. In the present work an evaluation is made of three Ransomware attacks: WannaCry, Jigsaw, and Petya. As an experimentation platform, a virtual network environment was used, which allows to identify how said attacks act in the encryption of information; for this, a hybrid network with WAN, LAN and DMZ segmentation was designed to propagate the malware by encrypting the information of the endpoints. The simulation tool used to design the network was GNS3. To evaluate the proposed attacks, a mechanism of controlled infection was developed, using samples of Ransomware shared on the web for educational purposes. Finally, the consumption of memory, CPU and bandwidth during the attack was evaluated, to determine which of these generates the greatest impact.